What Indonesia Should Learn from China's Social Credit System?: Measuring Government Authorities and Citizen’s Privacy Rights - Cokorda Istri Chandra Devi Padmananda; I Nyoman Suyatna (Faculty of law Udayana University, 2020)
China's Social Credit System (CSC) is a reputation system adopted by the Government of the Peoples’ Republic of China that establish a mechanism of rewarding and imposing punishment to its citizen, by taking into account the behavioral performance and compliance to the law and regulation. This article aimed to reviews the concept and the scope of implementation of China’s SCS and to analyze the possibility of the Indonesian Government to adopt it into Indonesia’s legal system and legal culture. This article reflects a doctrinal legal research that collects primary and secondary sources and uses statutory, comparative, and analytical approaches. This article found that SCS basically aims at creating a comprehensive data based-system to improve the citizen's behavior based on the scoring system that entails rewards and sanctions. The widely accepted of this system by the citizen of PRC, however, does not correspond to a remaining legal issue about the lack of protection of privacy rights, particularly regarding the naming and shaming of a blacklisted person. This article suggests that Indonesia may adopt some China’s SCS aspects, including the basic idea of the upgrading of the standard of citizen behavior, the establishment of a comprehensive system that integrating all data, and partial adoption of the data analysis. However, it seems that the naming and shaming for blacklisted persons do not relevant to be adopted by the Indonesian government in the near future, in a consideration of the legal culture in Indonesia and the communal life of the Indonesian peoples.